Revolusi Mental dalam Mengubah Pola Pikir Tenaga Pendidik dari Segi Perspektif Islam - Siti Makhmudah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
In recent years, the government is busy intensify mental revolution program. The budget disbursed for this program amounted to Rp140 billion, was allocated to ad creation, films, and public dialogue, to provide a space of religious leaders in order to more talk about behavior change that leads to positive. The program will run cross-sector under the Ministry of Religious Affairs, Ministry of Social Affairs, and the Ministry of Education, headed by Puan Maharani. PMK Sesmenko Sugihartatmo in a press conference at the Office of the Coordinating Ministry PMK, Thursday (27/08/2015), said the mental revolution translated Kemenko PMK as an attempt to change perspective, mindset, attitudes, values, and behavior of the Indonesian nation. It is also to make Indonesia a sovereign, independent, and personality. According to him, the use of instruments website is only one of a number of programs of the National Revolutionary Movement Mental. Other programs include public outreach and communication, coordination with the regional center, secretarial and operational. Movement mental revolution is a national movement that has three nilai.Ketiga these values is integrity, work ethic, and a spirit of cooperation royong.Sebagai guidelines for the community mental revolution, has been compiled book Philosophical Basis and General Handbook of Mental Revolution. Slogan mental revolution that is now being touted is as beautiful and effective for changes in mindset and attitude patterns all elements of this country to make the changes become more baik.Implikasi that can be felt but rarely recognized is, the emergence of moral degradation experienced by the people of this country. Many unfortunate case of sticking on the surface contained some mass media as well as quite disturbing of all parties, as well as showing the government's failure in coaching mindset and attitude pattern generation this country.